A Peep into Tourism Development in Zimbabwe: 1980-2010 - Zibanai ZHOU (Asian Economic and Social Society, 2023)
This paper reports on the findings of an exploratory study on the level of tourism development in Zimbabwe from 1980 to 2010. I have decided to highlight both positive and negative developments in this delicate sector, and to review my recommendations based on projected performance.The study’s data collection instruments were personal observations, questionnaire, follow up interviews and document analysis.The study’s key finding confirmsthat tourism development in Zimbabwe is in the front foot ascompared to the regional peers. The transformation of the ZTA, the coming on board of the mandatory tourism levy, an explicit national tourism policy and superb human resource training and skill development for the tourism sector and consequently, an uptick in tourism traffic into the country are landmark developments. On the down side, it is also found that the 2 per cent tourism lev developed a wall between operators and the regulatory authority. Operators have expressed the need for sharpened and more focused marketing strategies by the national tourism agency. It is concluded that tourism players are upbeat about prospects for the sector in the medium to long term.The study ends with recommendations and indication of future research priorities